Obesity is associated with severe COVID-19 - Ni Gusti Made Anggreni Nur Hadi; Carolina Paolin Kanaga (Indonesian Nutrition Association, 2022)
Diabetes mellitus, hypertension, and coronary artery disease (CAD) are comorbidities for severe COVID-19. Recently, there has been higher need for admission to intensive care unit (ICU), requiring oxygen support with high flow nasal cannula (HFNC), non-invasive ventilation (NIV), and invasive mechanical ventilation (IMV) amongst COVID-19 patients with obesity. The relationship between obesity and severe dyspnoea in COVID-19 needs more investigation.